Simulation of Light Intensity and Nano-Resistor Distribution in SSI-LEDs Using Python as a Framework. (1st August 2022) - Samuel, A.; Kuo, Y.
Abstract : The solid-state incandescent LED is a device that emits broad spectrum warm white light from nano-resistors through black body radiation. Previously, the steady state operation of the device was simulated with the finite element analysis method using COMSOL Multiphysics, while the light intensity distribution was separately simulated using MATLAB. There were limitations in these studies with respect to the number, size variation, and distribution of nano-resistors. In this paper, a new Python framework is developed to simulate light emission and perform COMSOL simulations for the same nano-resistor arrangement. The framework circumvents the nano-resistor count and distribution limitations in previous studies. This allows for more sophisticated simulations of many more nano-resistors than previously possible, and investigation into the effect of nano-resistor count on the device.